2019
DOI: 10.1002/jcb.28863
|View full text |Cite
|
Sign up to set email alerts
|

Blood circRNAs as biomarkers for the diagnosis of community‐acquired pneumonia

Abstract: Circular RNAs (circRNAs) have been reported as effective diagnostic and therapeutic biomarkers in many diseases, but the potential of using this easy‐to‐monitor and highly stable materials for diagnosing Community‐acquired pneumonia (CAP) remains unexplored. Here, aiming to identify potential CAP‐related circRNAs in peripheral blood and seeking to deepen the understanding of how circRNA‐miRNA‐mRNA regulatory networks may contribute to CAP, we applied microarrays profiling analysis and identified 8296 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…A handful of circRNAs have been revealed to participate in the regulation of pneumonia (Zhao et al 2019;Zhong et al 2019). For instance, Jia et al (2020) stated that circ_406961 inhibited the particulate matter (PM)-induced inflammatory response in human bronchial epithelial 16HBE cells by interacting with ILF2 and activating the STAT3/JNK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of circRNAs have been revealed to participate in the regulation of pneumonia (Zhao et al 2019;Zhong et al 2019). For instance, Jia et al (2020) stated that circ_406961 inhibited the particulate matter (PM)-induced inflammatory response in human bronchial epithelial 16HBE cells by interacting with ILF2 and activating the STAT3/JNK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulated hsa_circ_0089172 expression was confirmed using RT-qPCR, whilst in vitro experiments revealed that hsa_circ_0089172 could be a potential diagnostic biomarker, as it plays a crucial role in the pathogenesis of Hashimoto's thyroiditis by sponging miR-125a-3p. Zhao et al ( 37 ), Qian et al ( 38 ) and Wang et al ( 39 ) assessed differences in the circRNA expression level of peripheral blood samples from patients with community-acquired pneumonia, active pulmonary tuberculosis, and in patients who were small for their gestational age, respectively, with their results suggesting that circRNAs could be reliable biomarkers for diagnosing these conditions. Notably, to the best of our knowledge, the effects of aberrant circRNA expression on ISS has not been investigated, even though an increasing number of studies have investigated the functions of circRNAs in diseases ( 34 - 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis can guide clinical medication to effectively treat MI and signi cantly improved their prognosis. circRNAs have already been con rmed as effective biomarkers for numerous diseases, such as cancer [33], acquired pneumonia [34], Kawasaki disease [35]. It was reported that hsa_circ_0004104 was upregulated in coronary artery disease (CAD), and its overexpression might contribute to the pathogenesis of CAD [36].…”
Section: Discussionmentioning
confidence: 99%